Is patient insurance type related to physician recommendation, administration and referral for adult vaccination? A survey of US physicians. Issue 9 (2nd September 2019) - McNamara, Michelle; Buck, Philip O.; Yan, Songkai; Friedland, Leonard R.; Lerch, Kristin; Murphy, Alysa; Hogea, Cosmina
ABSTRACT: This study evaluated physician practices and perceived barriers for influenza, tetanus, diphtheria, pertussis (Tdap), and zoster vaccination of adults in the United States (US), with emphasis on patients with Medicare versus commercial insurance. A cross-sectional internet-based survey of board-certified general/family practitioners and internists (N = 1, 000) recruited from a national US physician panel was conducted in May 2017. For influenza, rates of physician recommendation (84% of Medicare patients, 82% of commercially-insured patients), administration (80% Medicare, 78% commercial), and referral (11% Medicare, 11% commercial) were similar regardless of insurance type. Tdap recommendation was higher for commercial compared to Medicare patients (59% vs. 54%, p < 0.001); while zoster recommendation was higher for Medicare patients than commercial (59% vs. 55%, p < 0.001). For Tdap and zoster, higher administration rates were reported in commercial patients (64% Tdap, 36% zoster) than Medicare (56% Tdap, 32% zoster), and referral rates were higher for Medicare patients (19% Tdap, 49% zoster) than commercial (14% Tdap, 42% zoster). Over 40% of physicians would be much more likely to administer Tdap and zoster vaccines if they were covered under Medicare Part B, with more physicians indicating financial barriers as "major" or "moderate" for Medicare than commercial patients. These differences may be related to financial barriers associated with adult vaccinations that are covered under Medicare Part D and involve patient out-of-pocket costs. Efforts to reduce financial barriers associated with adult vaccinations covered under Medicare Part D and to improve patient and physician knowledge could positively impact physician recommendation, administration, and referral for adult vaccination in the US.